Investigation of the direct recyclability of chip waste by cold cup extrusion and identification of its potential in continuous processes - Zettl, Bastian; Kraus, Martin; Böhm, Wolfgang; Zippert, Patrick; Merklein, Marion (Forming Technology Forum 2022, 2022)
Environmental protection and the responsible use of natural resources are currently the main challenges facing our society. When machining metallic materials, the formation of chips is unavoidable caused by technological reasons. This leads to a large proportion of chip waste. This waste needs to be subsequently recycled in energy-intensive cleaning and melting processes. To face these, this work is dealing with a novel direct recyclability method of chips from technically pure aluminum EN AW-1050A and pure copper CW004A by cold cup extrusion. The cups are characterized in regard to their bonding quality by light microscopy and X-ray analysis in order to prove the feasibility of the method. The objective is to demonstrate the suitability of cold cup drawing for creating cohesive bonds even under varying chip properties. Additionally, the usage of chip waste for recycling without melting in a continuous forming process is analyzed. For this, the so called Temconex® method is introduced, which enables the production of semi-finished profiles by a combination of friction and severe plastic deformation in an extrusion process.<br
Keywords: recycling; chips; cyclic economy; extrusion; sustainability; aluminum; copper